Mit gespaltenen Zungen – Eine vergleichende Untersuchung der Facebook-Auftritte der rechtspopulistischen Parteivorsitzenden Riikka Purra und Alice Weidel vor dem Hintergrund des Femonationalismus-Konzepts - Niedling, Christian (Germany, 2025)
The concept of femonationalism (Farris 2017) refers to the "strategic appropriation of feminist ideals for anti-Muslim politics" (cf. Dombrowski / Hajek 2021: 43). The model is currently being studied primarily in political and social science contexts, but increasingly also in linguistics. This article analyzes selected programs of the right-wing populist AfD (Germany) and the Perussuomalaiset (PS, Finland) as well as the Facebook appearances of their chairpersons (Alice Weidel and Riikka Purra) with regard to possible patterns and similarities. The question is whether and to what extent femonationalist strategies characterize the posts of the aforementioned politicians and to what extent differences can be found in the Facebook representations. Following Reisigl (Reisigl 2020), the principle of "calculated ambivalence" is applied here.